Implementing pelvic floor muscle training in women's childbearing years: A critical interpretive synthesis of individual, professional, and service issues. Issue 2 (17th December 2019) - Salmon, Victoria E.; Hay‐Smith, E. J. C; Jarvie, Rachel; Dean, Sarah; Terry, Rohini; Frawley, Helena; Oborn, Eivor; Bayliss, Susan E.; Bick, Debra; Davenport, Clare; MacArthur, Christine; Pearson, Mark
Abstract: Aims: Antenatal pelvic floor muscle training (PFMT) may be effective for the prevention and treatment of urinary and fecal incontinence both in pregnancy and postnatally, but it is not routinely implemented in practice despite guideline recommendations. This review synthesizes evidence that exposes challenges, opportunities, and concerns regarding the implementation of PFMT during the childbearing years, from the perspective of individuals, healthcare professionals (HCPs), and organizations. Methods: Critical interpretive synthesis of systematically identified primary quantitative or qualitative studies or research syntheses of women's and HCPs attitudes, beliefs, or experiences of implementing PFMT. Results: Fifty sources were included. These focused on experiences of postnatal urinary incontinence (UI) and perspectives of individual postnatal women, with limited evidence exploring the views of antenatal women and HCP or wider organizational and environmental issues. The concept of agency (people's ability to effect change through their interaction with other people, processes, and systems) provides an over‐arching explanation of how PFMT can be implemented during childbearing years. This requires both individual and collective action of women, HCPs, maternity services and organizations, funders and policymakers. Conclusion: Numerous factors constrain women's and HCPs capacity to implement PFMT. It is unrealistic to expect women and HCPs to implement PFMT without reforming policy and service delivery. The implementation of PFMT during pregnancy, as recommended by antenatal care and UI management guidelines, requires policymakers, organizations, HCPs, and women to value the prevention of incontinence throughout women's lives by using low‐risk, low‐cost, and proven strategies as part of women's reproductive health.